Balanced fluid regime versus saline-based fluid regime in post operative severe traumatic brain injury patients: acid base and electrolytes assessment - Hassan, Mohamad Hasyizan (2015)

(untitled)
Background: Normal Saline is a common fluid of choice in neurosurgery and neurointensive care setting. It is widely being used as resuscitative and maintainence fluid due to its isoosmolarity to prevent development of cerebral oedema and secondary insult that worsened the outcome of post traumatic brain injury patients. However, balanced solution was invented with closer properties to plasma content gives a new alternative for fluid management in neurointensive care setting Objectives: This study aimed to compare between balanced and saline fluid regime on electrolytes, acid base, serum osmolarity and outcome in post operative traumatic brain injury patients in neurointensive care setting. Methodology: This is a prospective, randomized and single blinded trial on 64 patients underwent operation for severe traumatic brain injury and subsequently ventilated in neurointensive care for more than 24 hours. Group B only received balanced fluid (Sterofundin ISO ®) while group S received Normal Saline as the maintenance fluid in the ICU over 24 hours. Electrolytes and acid base parameters were assessed at 8 hours interval over 24 hours period whereas the serum osmolarity and IVC was taken at admission and after 24 hours of ICU stay. The outcomes of the patients were assessed up to 3 months period post hospital discharge. Results: In term of serum sodium level, there were significant differences in time comparison in normal saline and balanced group (F=11.23, p<0.001). As for chloride, results showed that there were significant differences in normal saline and balanced group in time comparisons (F=9.02, p<0.001). There was significant difference in mean chloride level between two different groups at 0 hours, 8 hours and 24 hours (p<0.001) based on time (time-treatment interaction) where normal saline resulted to increase while balanced solution leads to reduce chloride level from baseline. Regarding potassium, there were significant differences in mean difference in normal saline group at time comparisons (F=7.56, p<0.001). There was significant difference of mean serum potassium among two different group based on time (F= 6.88, p<0.001) at 8 hours and 24 hours where saline fluid leads to slight hypokalemia while balanced solution has stable potassium level compared to baseline. Furthermore, we found that there were significant differences only in normal saline group in term of serum calcium level (F=0.76, p=0.015). There was significant difference in mean calcium concentration between saline and balanced fluid group at 24 Hr (p=0.003) with reduction trend in the former compared to baseline. The results showed that there was significant difference of magnesim level in both treatment groups on time comparisons (F=2.65, p=0.050). Upon within-between group comparison (time treatment interaction), there were significant differences seen at 0, 16 and 24 hours(F= 10.36, p<0.001). Concerning serum paCO2 level, the results showed that there was significant difference in normal saline group at time comparisons (F=3.78, p=0.020). There was significant difference of mean arterial pCO2 level among two different group based on time (F= 4.89, p= 0.004) at 0, 8 and 16 hours. In balanced solution group, there were significant difference in two comparisons in Base Excess level based of time (F=4.05, p=0.011). In time-treatment interaction, there was significant difference of base Excess concentration among two different group based on time (F= 2.78, p=0.049) at 0, 16 hours and 24 hours. In balanced solution group, there was significant difference of serum bicarbonate level based on time (F=5.94, p=0.001). There are significant difference of bicarbonate level (p=0.019) in between two groups with the mean difference of 1.15(0.20, 2.11) regardless of time. There was also significant time-treatment interaction (F= 4.65, p=0.031) in between those two group after infusion of fluids at 16 hours and at 24 hours duration. Regarding lactate level, there was a significant difference of mean lactate concentration within both treatment groups (F=25.62, p<0.001) based on time. Serum osmolarity after infusion of Normal Saline over 24 hours is significant (p<0.001) with the mean difference of 12.49(8.15, 16.12). Both mean difference of the IVC diameter after infusion of Normal Saline and balanced solution is statistically significant with the mean difference of 0.11cm(0.08, 0.14) (p<0.001) and 0.13cm(0.10, 0.16)(p<0.001) respectively. Concerning the outcome, there was no significant difference in the patients outcome between both groups. Conclusion: In conclusion, the saline based fluid leading more towards higher chloride and lower pH and Base Excess than balanced group. In contrast, balanced fluid resulted to more towards maintaining higher potassium, calcium, magnesium and bicarbonate level than saline fluid. Normal serum osmolarity is preserved in both groups. There was significant improvement of the IVC diameter in both fluid therapies. The outcome of the patients between both groups is insignificant.